Hazards of diethyl phthalate (DEP) exposure: A systematic review of animal toxicology studies - Weaver, James A. (Environ Int, 2020)
BACKGROUND: Diethyl phthalate (DEP) is widely used in many commercially available products including plastics and personal care products. DEP has generally not been found to share the antiandrogenic mode of action that is common among other types of phthalates, but there is emerging evidence that DEP may be associated with other types of health effects. OBJECTIVE: To inform chemical risk assessment, we performed a systematic review to identify and characterize outcomes within six broad hazard categories (male reproductive, female reproductive, developmental, liver, kidney, and cancer) following exposure of nonhuman mammalian animals to DEP or its primary metabolite, monoethyl phthalate (MEP). METHODS: A literature search was conducted in online scientific databases (PubMed, Web of Science, Toxline, Toxcenter) and Toxic Substances Control Act Submissions, augmented by review of online regulatory sources as well as forward and backward searches. Studies were selected for inclusion using PECO (Population, Exposure, Comparator, Outcome) criteria. Studies were evaluated using criteria defined a priori for reporting quality, risk of bias, and sensitivity using a domain-based approach. Evidence was synthesized by outcome and life stage of exposure, and strength of evidence was summarized into categories of robust, moderate, slight, indeterminate, or compelling evidence of no effect, using a structured framework. RESULTS: Thirty-four experimental studies in animals were included in this analysis. Although no effects on androgen-dependent male reproductive development were observed following gestational exposure to DEP, there was evidence including effects on sperm following peripubertal and adult exposures, and the overall evidence for male reproductive effects was considered moderate. There was moderate evidence that DEP exposure can lead to developmental effects, with the major effect being reduced postnatal growth following gestational or early postnatal exposure; this generally occurred at doses associated with maternal effects, consistent with the observation that DEP is not a potent developmental toxicant. The evidence for liver effects was considered moderate based on consistent changes in relative liver weight at higher dose levels; histopathological and biochemical changes indicative of hepatic effects were also observed, but primarily in studies that had significant concerns for risk of bias and sensitivity. The evidence for female reproductive effects was considered slight based on few reports of statistically significant effects on maternal body weight gain, organ weight changes, and pregnancy outcomes. Evidence for cancer and effects on kidney were judged to be indeterminate based on limited evidence (i.e., a single two-year cancer bioassay) and inconsistent findings, respectively. CONCLUSIONS: These results suggest that DEP exposure may induce androgen-independent male reproductive toxicity (i.e., sperm effects) as well as developmental toxicity and hepatic effects, with some evidence of female reproductive toxicity. More research is warranted to fully evaluate these outcomes and strengthen confidence in this database.